Preparation and low-temperature sintering of cu nanoparticles for high-power devices - Krishnan, S.; Haseeb, A.S. Md. Abdul; Johan, M.R. (2012)
One of the fundamental requirements for high-temperature electronic packaging is reliable silicon attach with low and stable electrical resistance. This paper presents a study conducted on Cu nanoparticles as an alternative lead-free interconnect material for high-temperature applications. Cu nanoparticles were prepared using pulsed wire evaporation technique in water medium. Pure Cu nanoparticles without any organic mixture were used in this paper. An economical approach to extract the nanoparticles from water was established. In situ Cu nanoparticles oxide reduction was successfully done using forming gas (N-2-5 H-2). Cross-section analysis on bonded interface shows onset of Cu nanoparticles sintering at 400 degrees C. We successfully demonstrated the possibilities of using Cu nanoparticles as silicon die attach material for high-temperature electronic devices.